The Microbial Sulfur Cycle at Extremely Haloalkaline Conditions of Soda Lakes - Sorokin, Dimitry Y. (Frontiers in Microbiology, 2011)
Microbial sulfur cycle is among the most active in soda lakes. Oxidative part of the cycle is driven by chemolithoautotrophic haloalkaliphilic sulfur-oxidizing bacteria. They are present at high number of up to 106 viable cells/cm3 and represented by four genera within the Gammaproteobacteria, Thioalkalivibrio, Thioalkalimicrobium, Thioalkalispira and Thioalkalibacter. The genus Thioalkalivibrio is the most physiologically diverse and covers whole spectrum of salt/pH conditions present in soda lakes. The dominant subgroup of this genus is able to grow in saturated soda brines containing 4 M total Na+ - a unique property for any known aerobic chemolithoautotrophs. Some of the species can use thiocyanate as a sole energy source and 3 species out of 9 can grow anaerobically with nitrogen oxides. The reductive part of the cycle is also active in anoxic sediments of various soda lakes. In situ and laboratory experiments showed high sulfate reduction rates only hampered at salt-saturated conditions. The highest rates of sulfidogenesis were observed with elemental sulfur followed by thiosulfate. Formate was the most efficient electron donor with all three sulfur electron acceptors, while acetate was only utilized as an electron donor at sulfur-reducing conditions. The soda lake sulfidogenesis showed obligately alkaliphilic pH response matching the in situ conditions. Microbiological analysis showed a domination of three groups of haloalkaliphilic autotrophic SRB belonging to the order Desulfovibrionales with a clear tendency to grow by thiosulfate disproportionation even at salt-saturating conditions. Few novel representatives of the order Desulfobacterales capable of heterotrophic growth with VFA and alcohols at high pH and moderate salinity have also been found, while acetate oxidation was a function of a specialized group of haloalkaliphilic sulfur-reducing bacteria belonging to the phylum Chrysiogenetes.